Challenges in the diagnosis of primary squamous cell carcinoma of the prostate: a case report and literature review - Song, Shengyou; Song, Yalin (Frontiers in Surgery, 2025)
IntroductionProstate squamous cell carcinoma (SCCP)is a rare malignancy that accounts for 1% of prostate cancer cases. In resource-limited settings, it is often at an advanced stage due to the limitations of PSA/imaging-based methods, and pathological confirmation is needed for a definitive diagnosis, particularly in elderly patients with comorbidities.Case PresentationA 71-year-old male with benign prostatic hyperplasia presented with urinary obstruction confirmed by urine flowmetry. Digital rectal examination of the prostate revealed severe enlargement, a firm consistency and an irregular surface; B-mode ultrasonography revealed calcifications without focal lesions. Laboratory tests revealed hematuria, elevated RBC counts, reduced WBC counts, normal serum PSA, and negative microbiological cultures. Cystoscopy revealed bladder wall thickening with multiple diverticula, suggesting chronic obstructive sequelae. Through physical, laboratory, and imaging examinations, we diagnosed the patient with benign prostatic hyperplasia before surgery. The postoperative pathological diagnosis was SCCP. The patient was discharged 7 days post-surgery and treated for prostate cancer (PCa) at a higher-level hospital.Conclusionin vivo fluorescence imaging and laboratory examination of PCa targets are needed to further promote noninvasive PCa diagnosis.